Environmental Rehabilitation Through Community-Based Mangrove Replanting Action As A Sustainable Fisheries Campaign: A Case Study At Binanga Sangkara, Maros, South Sulawesi - Achmad Fuad Fathurrahman; Idham Malik; Amriana Amriana (Journal of Aquaculture Science, 2021)
Mangrove, a unique ecosystem commonly situated on the coast, has a very vital role for the living creatures both inhabiting in and around the ecosystem. As the biggest mangrove forest holder in the world, Indonesia owns its great potential for both sustainable fisheries and community welfare. In order to preserve the mangrove ecosystem for sustainable fisheries, environmental improvement through mangrove rehabilitation program is important. WWF Indonesia collaborated with PT. Bogatama Marinusa (PT. Bomar) implement a mangrove rehabilitation program to support ASC (Aquaculture Stewardship Council) shrimp certification. The activity was implemented on 2019 at Binangasangka, Maros, South Sulawesi. The program was implemented in several steps namely planning, consolidation to communities, socialization and local support, seed preparation, planting, and monitoring and evaluation. The whole program has engaged multiple local environment-concern communities, especially youth community, and have collaborated significant local stakeholders namely the Institute of Brackish Aquaculture Research of Maros and the Technology University of Sulawesi, as well embraced local society. In the end, about 24 thousand mangrove seeds have been planted and covering up to 1 hectare. From the mentioned number, the successfully survived seeds have reached 74 % and hopefully well-settled in future. The overall activities were expected to contribute not only expanding mangrove coverage in coastal area, but also being the educational tools about environmental awareness to young generation. Keywords: mangrove, rehabilitation, community, Maros.